NILAI TAUHID PADA TOKOH AYYAS DALAM NOVEL BUMI CINTA KARYA HABIBURRAHMAN EL SHIRAZY - Sumiharti Sumiharti; Eki Yuniarti (Universitas Batanghari, 2021)
The purpose of this research describes the value of tawhid in the character of Ayyas in the novel Bumi Cinta by Habiburrahman El Shirazy, which refers to three aspects, namely: (1) aspects of the realization of the value of rububiyah tawhid, (2) aspects of the realization of the value of tawhid uluhiyah, and (3) aspects of the realization of the value of tawhid nature. This research includes qualitative descriptive research/. The data used in this research is primary data because the novel's utterances represent the aspects of the embodiment of the value of tawhid in the character of Ayyas in the novel Bumi Cinta by Habiburrahman El Shirazy. Based on the results of research, it can be concluded that the value of tawhid in the character of Ayyas contained in the novel Bumi Cinta by Habiburrahman El Shirazy refers to three aspects, namely: (1) Aspects of the realization of the value of tawhid rububiyah illustrated in the belief in the figure of Ayyas who always believed in God is God. Ayyas believed that Allah was the almighty and entitled to him. The whole aspect of the embodiment of the value of rububiyah tawhid is illustrated in 31 quotations. (2) Aspects of the image of the value of tawhid uluhiyah are depicted in the figure of Ayyas, who believes in God in the form of worship in prayer, prayer, fasting, tawakkal, repentance, love, fear, hope, and various other worships. The entirety of this aspect is illustrated in 71 quotations. (3) The realization of the value of tawhid nature is described in the actions of the figure of Ayyas, who always mentions the nature of God in every word. The entirety of this aspect is illustrated in 10 quotations.